(untitled) (Communications in Mathematical Research, 2021)
In the paper we introduce the notions of the separation factor κ and give a representive of metric projection on an n-codimension subspace (or an affine set) under certain conditions in Banach space. Further, we obtain the distance formula from any point x to a finite n-codimension subspace. Results extend and improve the corresponding results in Hilbert space.